Eski Türkçe ile İrani diller arasındaki söz denklikleri - Özer, Canan (My University, 2022)
Tarih boyunca siyasi, coğrafi, ticari ve dini ilişkilere sahip olan Türkler ve İrani halklar pek çok alanda birbirilerinden etkilenmişlerdir. Doğal olarak Türkçe ve İrani diller de bu sosyal ve kültürel ilişkiler bağlamında dil etkileşimi yaşamışlardır. Çalışmanın konusu bu etkileşim çerçevesinde Eski Türkçe ve İrani dillerin söz denklikleri ve kavram alanlarının tespitidir. Çalışmada Eski Türkçe dönemine ait metinlerin taranması ve ilgili kaynaklara başvurulması suretiyle söz denklikleri tespit edilmiş ve bu sözcükler hakkında köken bilimsel görüşler sunulmuştur. Kavramsal alan dizini eklenerek bu sözcüklerin kavram alanları gösterilmiştir. Sonuç kısmında çalışmadan elde edilen bilgiler değerlendirilmiştir.

Turks and Iranian peoples, who have had political, geographical, commercial and religious relations throughout history, have been influenced by each other in many areas. Turkish and Iranian languages have also experienced language interaction in the context of these social and cultural relations. The subject of the study is the determination of the word equivalence of Old Turkish and Iranian languages and their conceptual fields within the framework of this interaction. The aim of the thesis is to determine the Iranian word equivalences of Turkish in the Old Turkish period, to determine the concept areas of these words and to evaluate the language relations through them. In the study, Iranian word equivalences were determined by scanning the texts of the Old Turkish period and referring to the relevant sources, and the scientific opinions about these words were presented in the index. By adding a conceptual field index, the subject distributions of these words were examined. In the conclusion part, the information obtained from the study was evaluated.
Keywords: Concept Area; Dil ve diller; Eski Türkçe; History and criticism; Iran; Iranian Languages; İran; İrani Diller; Kavram Alanı; Language and languages; Old Turkish; Relations between Turkish-Iranian Languages; Söz Varlığı; Tarih ve eleştiri; Turkish language; Turkish literature; Türk dili; Türk edebiyatı; Türkçe-İrani Diller İlişkileri; Vocabulary